Faktor Faktor yang Memengaruhi Terjadinya Asphyxia Neonatorum di Rumah Sakit Umum St Elisabeth Medan 2007 - 2013 - herianto chou; Sori Muda Sarumpaet; Rasmaliah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
The incidence of neonatorum asphyxia is a condition where the baby can not breathe spontaneously and regularly after birth. Infants with neonatorum asphyxia if not given immediate nursing actions, it would be fatal to their survival. It was estimated that approximately 27% of all neonatal deaths worldwide were caused by neonatorum asphyxia. This study aims to determine the factors that influence the occurrence of neonatorum asphyxia at St Elisabeth Hospital Medan in 2007-2012. This type of observational analytic study with case-control design with a sample of cases and controls amounted to 156 babies. Data analysis methods used include bivariate analysis using chi-square and multivariate analysis using logistic regression. Results of this study showed that the incidence significantly Asphyxia neonatorum at St Elisabeth Hospital Medan influenced by maternal age, maternal parity, history of maternal anemia at delivery and birth weight babies. Logistic regression analysis to get the factors have the most dominant factor is maternal age (OR 2.51, PAR 14,2%, 95% CI 1.60 to 10.58), parity (OR 3.12, PAR 14,8%, 95% CI 1.09 to 7.53) and infant birth weight (OR 3.51, PAR 7,4%, 95% CI 1.26 to 9.7). To prevent the incidence of neonatal asphyxia expected on health care workers and stakeholders such as the Badan Kependudukan dan Keluarga Berencana Nasional (BKKBN) to provide education and socialization regarding the optimal age to become pregnant from variety of information media, pregnant women do recommend at least 4 times antenatal care during pregnancy and ongoing training on the management of neonatal asphyxia in newborns.